Modelling and in-situ measurement of dynamic behavior of asphalt supporting layer in slab track system. (20th December 2019) - Liu, Song; Chen, Xianhua; Ma, Yuewei; Yang, Jun; Cai, Degou; Yang, Guotao
Highlights: Application of asphalt supporting layer in slab track system. Dynamic responses of asphalt supporting layer under moving train load. In-situ measurement from practical railway line to validate the FE model. The optimal range of thickness of asphalt supporting layer for slab track system. Abstract: During the last decades, asphalt concrete has been introduced in both ballast and ballastless track (including but not limited to slab track) systems. The use of asphalt concrete provides better damping and waterproofing performance. For this reason, a supporting layer of asphalt concrete (ASL) was introduced to the latest Chinese slab track system. In this paper, an in-depth study of the dynamic behavior of ASL was presented using modelling and in-situ measurement approaches. In the FE model, the train load was simplified to be a time series of concentrated load on rail nodes, and asphalt concrete was modeled as viscoelastic material by Prony series. The FE model was validated against in-situ measurement on a test section, in which a monitoring system was setup during construction. A series of transient analysis were conducted to obtain the dynamic responses of ASL under moving train load. The parametric effects of thickness of ASL was also studied with respect to the dynamic responses of superstructure and substructure, as well as the stability and durability of ASL. The results showed that, under moving bogie load, the reach of the dynamic responses in ASL is about 7.5 m in the longitudinal direction, and the maximum values occur at the position beneath the rails. A thicker ASL is more favorable to ride comfort and structural stability of high-speed railway track system. However, considering the economic and construction factors, an optimal thickness range of 7–10 cm is suggested for ASL in CRTS III slab track.